Modeling and prediction for the oxidation efficiency of magnesium sulfite in aeration tank of magnesium-based seawater exhaust gas clean system. (February 2019) - Liu, Quan; Zhu, Yimin; Li, Tie; Tang, Xiaojia; Liu, Weifeng; Guo, Lin; Zhao, Jiao
In magnesium-based seawater exhaust gas clean system, the desulfurization by-product, magnesium sulfite (MgSO3 ), has a negative impact on the ecological environment, which needs to be treated to make harmless. Due to the limited space on board, the aeration oxidation method is used to convert it to magnesium sulfate. Because of the variable size, shape and flow field of aeration tank, it is difficult and expensive to design and verify the oxidation efficiency of the aeration tank by experimental method. In this work, in order to predict the oxidation efficiency accurately, RFlow, a computational fluid dynamics software, was used to analyze the flow field and MgSO3 oxidation reaction in aeration tank. The subdomain technology was adopted for physics modeling and mesh generation of the aeration tank, and the total number of meshes was 285, 000. The multi-phase flow field model was set up using the multi-fluid model and dispersive k-ε turbulence model. Under the given initial conditions, the predicted oxidation efficiency was 94.2%. Compared with the results of the actual ship test, the prediction model for MgSO3 oxidation efficiency of the aeration tank is reliable.